2016
DOI: 10.1111/vco.12210
|View full text |Cite
|
Sign up to set email alerts
|

Potency and stability of compounded cyclophosphamide: a pilot study

Abstract: Compounding of drugs for use in veterinary oncology is becoming increasingly common. We obtained 15 mg cyclophosphamide capsules from five different compounding pharmacies and performed potency analyses at two time points, as well as stability at 60 days. Potency results for four out of five and zero out of five (4/10) samples analysed were inadequate. Stability at 60 days was acceptable for all but one sample. This pilot study raises several important points of concern when compounding chemotherapy in dogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Recent studies (Burton et al . , Robat & Budde , KuKanich et al . ) found that compounded drugs may contain suboptimal levels and the concentration of a compounded drug can vary more than 10% of the intended dose.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Burton et al . , Robat & Budde , KuKanich et al . ) found that compounded drugs may contain suboptimal levels and the concentration of a compounded drug can vary more than 10% of the intended dose.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in potency and stability of compounded drugs could potentially arise from a number of factors including the drugs being compounded, whether the compounding is performed from the FDA‐approved product or a bulk substance, the compounding technique and storage duration and conditions. A previous study evaluating the potency and stability of compounded cyclophosphamide demonstrated that 4 of 10 samples of compounded cyclophosphamide evaluated were <90% of labelled concentration at initial testing, with a fifth sample with a potency of <90% of labelled concentration after a 60‐day stability period . All samples of compounded cyclophosphamide obtained in this study were within 90%‐110% of labelled concentration both at baseline and at the 6‐week time point; however, 3 samples had decreases in potency of 6.2%, 7.5% and 12.6% over the 6‐week period.…”
Section: Discussionmentioning
confidence: 58%
“…Despite wide use clinically, the potency and stability of compounded oral chemotherapy drugs have not been extensively evaluated to date. A recent publication demonstrated that 40% of samples of compounded cyclophosphamide had an actual potency that was greater than ±10% the labelled concentration of drug; 1 sample had a potency of <10% of labelled concentration 60 days after receipt, indicating that stability of compounded chemotherapy drugs may be an issue as well . This study raises further concern that compounded chemotherapy agents may not be as stable or as potent as their FDA‐approved product.…”
Section: Introductionmentioning
confidence: 76%
“…An important limitation of the current study was the variation in CP dosing among individual dogs, with a mix of oral pulse (~250 mg/m 2 q2‐4 weeks) and metronomic (~15 mg/m 2 q24h) protocols. Actual pulse dosages varied based on tablet size, and many of the metronomic doses were compounded, which could affect the potency of dose given . Without measuring plasma or urinary concentrations of CP and its metabolites, we could not account for variability in dosing from imprecisely compounded formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Actual pulse dosages varied based on tablet size, and many of the metronomic doses were compounded, which could affect the potency of dose given. 29 Without measuring plasma or urinary concentrations of CP and its metabolites, we could not account for variability in dosing from imprecisely compounded formulations. In addition, we did not collect urine-specific gravity data, which could influence SHC risk.…”
Section: Discussionmentioning
confidence: 99%